2018
DOI: 10.15406/hij.2018.02.00056
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing moringa cultivation in Tamil Nadu – an economic analysis

Abstract: Moringa (Moringa oleifera Lam.) is grown extensively in tropics and subtropics of India and Africa. It is widely used as vegetable and grown commercially for its edible pods and leaves. On realizing the nutritional importance, Moringa was used in different forms and hence the cultivation of Moringa is popular in different nations particularly in Tamil Nadu. The Factors influencing Moringa cultivation in Southern Districts of Tamil Nadu was carried out during 2016-17.1 The study revealed that presence of higher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 5 publications
2
0
0
Order By: Relevance
“…This meaning a percent increase in all inputs proportionally would bring the total production by more than a percent increase. This finding is similar to a result by Sekhar et al (2018) that indicated the increasing return to scale with 1.48 value in their study of the economic efficiency of Moringa in India.…”
Section: Parameter Estimates Of the Sfp Modelsupporting
confidence: 90%
See 1 more Smart Citation
“…This meaning a percent increase in all inputs proportionally would bring the total production by more than a percent increase. This finding is similar to a result by Sekhar et al (2018) that indicated the increasing return to scale with 1.48 value in their study of the economic efficiency of Moringa in India.…”
Section: Parameter Estimates Of the Sfp Modelsupporting
confidence: 90%
“…The level of labor and number of Moringa tree coefficient in the above SPF model implies that a percent increase in labor and number of Moringa tree increased the amount Moringa production by 92% and 36%, respectively. This result is similar to Sekhar et al (2018) of whom indicated the number of human labor used (man-days) per ha per annum was found to influence the yield of Moringa in India. The estimated value of gamma is 0.74 which implies that 74% of the total variation in Moringa production farm output is accounted for by technical inefficiency.…”
Section: Parameter Estimates Of the Sfp Modelsupporting
confidence: 89%